1999
DOI: 10.1073/pnas.96.10.5486
|View full text |Cite
|
Sign up to set email alerts
|

Solution structure and dynamics of a de novo designed three-helix bundle protein

Abstract: Although de novo protein design is an important endeavor with implications for understanding protein folding, until now, structures have been determined for only a few 25-to 30-residue designed miniproteins. Here, the NMR solution structure of a complex 73-residue three-helix bundle protein, ␣ 3 D, is reported. The structure of ␣ 3 D was not based on any natural protein, and yet it shows thermodynamic and spectroscopic properties typical of native proteins. A variety of features contribute to its unique struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
218
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(221 citation statements)
references
References 59 publications
(71 reference statements)
3
218
0
Order By: Relevance
“…The ground-breaking work of DeGrado and coworkers (17)(18)(19)(20) has led to the development of well packed helix bundle proteins with natural-like sequences and stabilizing interactions. In their work, and pioneering work from other laboratories, a specific fold has been achieved via the formation of tertiary hydrogen bonds (20)(21)(22)(23), crystal contacts (18,24), disulfide bonds (25,26) or favorable charge-charge interactions (19,20,23,24,26,27). Previous work toward simplifying proteins has shown that a native-like Src homology 3 fold can be achieved with chiefly five different residues (although 13 in total) (28), and a four-helix bundle protein can be formed from only nine different residues (29).…”
Section: The Presence Of An Aromatic Ring At the C Terminus Is Requirmentioning
confidence: 99%
“…The ground-breaking work of DeGrado and coworkers (17)(18)(19)(20) has led to the development of well packed helix bundle proteins with natural-like sequences and stabilizing interactions. In their work, and pioneering work from other laboratories, a specific fold has been achieved via the formation of tertiary hydrogen bonds (20)(21)(22)(23), crystal contacts (18,24), disulfide bonds (25,26) or favorable charge-charge interactions (19,20,23,24,26,27). Previous work toward simplifying proteins has shown that a native-like Src homology 3 fold can be achieved with chiefly five different residues (although 13 in total) (28), and a four-helix bundle protein can be formed from only nine different residues (29).…”
Section: The Presence Of An Aromatic Ring At the C Terminus Is Requirmentioning
confidence: 99%
“…Unfortunately, initial attempts to design proteins led to structures that formed molten globulelike states with dynamic behavior relative to natural proteins. More recently, it has been possible to design small uniquely folded proteins that incorporate all of the commonly occurring secondary structural and supersecondary structural motifs (29)(30)(31)(32)(33)(34)(35)(36). These studies illustrated the delicate interplay of forces that define the uniquely folded structures of proteins; hydrophobicity provides a strong driving force for folding, but designs based on this consideration alone often adopt dynamically averaging Abbreviations: DF1, Due Ferro 1; PDB, Protein Data Bank.…”
mentioning
confidence: 99%
“…Side-chain repacking algorithms search for combinations of amino acid side chains capable of packing together in efficient low-energy combinations. However, with a few exceptions (36,46), these methods have been used to redesign natural proteins rather than to engineer novel structures. Further, a major limitation of early side-chain repacking algorithms was their use of rigid backbone geometries, which placed somewhat artificial restrictions on the number of combinations of side chains that may be accommodated within a protein core.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both genetic algorithms and simulated annealing have been successfully applied to re-design a number of natural proteins: 434 Cro (Desjarlais & Handel, 1995), ubiquitin (Johnson et al, 1999), the B1 domain of protein G (Jiang et al, 2000), the WW domain (KraemerPecore et al, 2001), and helical bundles (Bryson et al, 1998;Jiang et al, 1997). In many cases, these methods have aided in identifying experimentally viable sequences (Kraemer-Pecore et al, 2001;Walsh et al, 1999). However, since stochastic search methods do not always identify global optima (Voigt et al, 2000), other search methods have also been developed.…”
Section: "Directed" Methods Of Protein Designmentioning
confidence: 99%